Evolution of the Soil Report Carbon / Nitrogen in Relation with the Severity of the Bunette Groove of Cassava (SBM) in Three Agrosystems of the Yakonde Set (Y2) in the Reserve of the Biosphere of Yangambi, DRC - Kombele M; Kombele B; Ofeka L; Kolela B; Motosia A.; Bati S; Bohula F.; Kombele F (Britain International for Academic Research (BIAR) Publisher, 2022)
The occupation of earth, dominated by the peasant fields of Obama cassava in forest zone on the Yakonde set (Y2) in Yangambi in Congolese central pan (RDC), change quickly and the forest fragmentation bound to the roving agriculture on the giblets-burnt lands became one of the processes dominating the landscape dynamics. In addition to the machete and the ax, fire remained for the agriculturists of the region an excellent means to get rid of the cut vegetation and also to lead physical and chemical modifications quickly in the superficial layers of soil. To put in evidence, the evolution of the values of the C/N report of soil in report to those of the severity of the brunette groove of cassava (SBM) that rages currently in Yangambi (CWAVE project), three agrosystèmes of the Yakonde set (Y2) have been chosen: the secondary forest (FS), the forest recrû (RF) and the grassy fallow (JH). In every in every different type of forests, an extent of 50m x 50m was there cut, arranged and without use of fire and the cuttings healthy and infected of SBM of the cassava of the Obama variety have been planted in lines simple oriented north-south in under-parcels in repeated at random two blocks. In 19 pedological pits of the experimental site, 76 pedological samples have been appropriated in two slices of soil: 0 - 20 cm and 20 - 40 cm of depth. The total organic nitrogen of soil has been measured out by the Kjeldhal method and the carbon, by the method to the bichromate of potassium by humid way and to cold weather (Kombele, 2004, Kakuni, 2020). as for the severity of SBM, she/it has been determined by observations on symptomatic leaves and without the symptoms according to the methods of Sseruwagi and al. (2005) and Mware and al. (2009). The results gotten to four months of age of Obama cassava show that the middle values of the C/N are raised more in the grassy fallow (JH) with 8,76±3,43 and a severity of the SBM of 2,7, consistent of those of the secondary forest (FS) with 7,26±3,37 the C/N and a severity of the SBM of 2,4, those of the forest recrû (RF) with 5,28±3,02 the C/N and a severity of the SBM of 2,1.